(untitled) (Research, Society and Development, 2020)
This work is a descriptive study, experience report type, that deals about the experience by academic members of the university extension project Heróis do Sorriso: Rescuing smiles with prevention and oral health promotion. The purpose of this report is to describe the performance of interactive, and playful activities, aimed at conditioning the target audience, in order to reduce the fear of the dental surgeon, in addition to encouraging the prevention of caries disease, the promotion of oral health, and autonomy in caution. The activities were developed by university students with children ranging from 5 to 12 years old, at the non-governmental organization (NGO) Operation Rescue located in the city of Patos - PB. The experience provided dentistry students a new way of working with oral health education, based on the practices carried out with children, in order to envision paths and performance scenarios, capable of renewing the exercise of the health educational process, in view of the overcoming punctual and linear care practices.